2005
DOI: 10.1103/physrevb.71.094105
|View full text |Cite
|
Sign up to set email alerts
|

Impurity-kink interaction in the two-dimensional Frenkel-Kontorova model

Abstract: The dislocation gliding in crystals with impurities is investigated by computer simulations for the two dimensional Frenkel-Kontorova model. It is shown that the impurity-dislocation interaction can result in both the stimulation of the double-kink formation (which increases the dislocation mobility) and the trapping of moving kinks by the impurities with the following kink-antikink recombination (which slows down the dislo cation motion). The relative importance of these competing mechanisms depend mostly on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…This behavior has also been observed for carbon additions in plain carbon steels [28,29]. Several authors [15][16][17]24,[31][32][33]36] have reported that during hot deformation, boron segregates towards austenitic grain boundary and promotes disordering and the consequent expected increase in grain boundary dislocations mobility, which in turn facilitates the onset of the DRX. Results obtained by the present authors [24,25] and reported information in steels [37,38] indicate that substitutional atoms tend to increase the activation energy for austenite deformation and consequently, to delay the onset of DRX, while interstitial atoms promote a diminution of the activation energy and therefore to accelerate the initiation of DRX [28,29].…”
Section: Steelmentioning
confidence: 59%
See 1 more Smart Citation
“…This behavior has also been observed for carbon additions in plain carbon steels [28,29]. Several authors [15][16][17]24,[31][32][33]36] have reported that during hot deformation, boron segregates towards austenitic grain boundary and promotes disordering and the consequent expected increase in grain boundary dislocations mobility, which in turn facilitates the onset of the DRX. Results obtained by the present authors [24,25] and reported information in steels [37,38] indicate that substitutional atoms tend to increase the activation energy for austenite deformation and consequently, to delay the onset of DRX, while interstitial atoms promote a diminution of the activation energy and therefore to accelerate the initiation of DRX [28,29].…”
Section: Steelmentioning
confidence: 59%
“…Therefore boron additions play a sort of solid solution softening. This softening mechanism can be related to the occurrence of an additional channel that facilitates formation of dislocations kinks at impurity centers (a decrease in kink energy with increasing solute content, facilitates the dislocation mobility) [31][32][33]. All these phenomena can also be explained on the basis of the non-equilibrium segregation theory proposed by Aust et al [34], as an effect of mobile vacancy-solute atom complexes diffusing through a vacancy gradient towards vacancy sinks (this gradient can be generated by cooling and/or by plastic deforma- 6.…”
Section: Resultsmentioning
confidence: 99%
“…The other is that the presence of impurities can increase the dislocation velocity, which leads to solid solution softening (SSS). By computer simulation, Gornostyrev et al [7] investigated the impurity-kink (the impurities are immobile substitution) interaction in the two-dimensional Frenkel-Kontorova model. They found that the presence of impurities can increase the dislocation velocity at low temperatures which leads to the SSS.…”
Section: Introductionmentioning
confidence: 99%
“…The SSS effect has been known for bcc transition metal alloys [15][16][17] . By computer simulation, Gornostyrev et al [18] ARTICLES CONDENSED STATE PHYSICS investigated the impurity-kink (the impurities are immobile substitution) interaction in the two-dimensional Frenkel-Kontorova model. They found that the presence of impurities can increase the dislocation velocity at low temperatures which leads to the SSS.…”
Section: Using the First-principles Self-consistent Discrete Variatiomentioning
confidence: 99%
“…The SSS effect has been known for bcc transition metal alloys [15][16][17] . By computer simulation, Gornostyrev et al [18] …”
mentioning
confidence: 99%